PENGARUH GAJI INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI RSUD ASY-SYIFA KABUPATEN SUMBAWA BARAT - Ahdi Topan Sofyan (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Asy-Syifa Regional General Hospital in West Sumbawa Regency, as a public health service institution, should have employees who are enthusiastic and motivated to work effectively and efficiently. The salaries and wages given need to be adjusted to the profession, education, and length of service of employees so that they are able to demonstrate high productivity in order to achieve the mission and goals that have been set. However, there are problems at Asy-Syifa Hospital related to the inconsistency in determining employee salaries, incentives, and work motivation. This happens because the salary given is not balanced with the expertise, education, or skills possessed by employees, thus reducing their response and interest in the tasks given by their superiors. The suboptimality in providing incentives and work motivation can be seen from the lack of employee enthusiasm in working, as well as low interest and positive attitudes towards work due to inappropriate rewards, which ultimately have an impact on suboptimal performance. This study aims to determine the effect of Salary, Incentives, and Work Motivation on Employee Performance. The focus of the study was Non-Permanent Employees at Asy-Syifa Hospital, West Sumbawa Regency, with 100 respondents as a sample taken using the Slovin formula. The data were analyzed using multiple linear regression with SPSS Version 27. The results of the study showed that Salary, Incentives, and Work Motivation partially and simultaneously had a significant effect on Employee Performance at Asy-Syifa Hospital, West Sumbawa Regency.